2017
DOI: 10.1177/0961203317693929
|View full text |Cite
|
Sign up to set email alerts
|

Gestational outcomes in patients with neuropsychiatric systemic lupus erythematosus

Abstract: This study analyzed maternal and fetal outcomes of pregnancies of neuropsychiatric systemic lupus erythematosus patients followed in a reference unit. This retrospective cohort study included 26 pregnancies of patients seen between 2011 and 2015 included with history and/or active neuropsychiatric systemic lupus erythematosus among 135 pregnancies. Three patients had active neuropsychiatric systemic lupus erythematosus at conception, but only one remained with neurological activity during gestation, characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…The observed fetal/neonatal outcome was similar to that of our cohort with a live birth rate between 80 and 90% and comparable complications. Other published studies from Latin American countries address specific groups of patients, such as the obstetric outcome in childhood-onset SLE, 55 serum laminin-111 levels in preeclampsia and lupus, 56 as well as the gestational outcome in neuropsychiatric lupus 57 . Furthermore, a controlled clinical trial with a small number of patients showed the benefit of hydroxychloroquine on SLE activity during pregnancy 37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed fetal/neonatal outcome was similar to that of our cohort with a live birth rate between 80 and 90% and comparable complications. Other published studies from Latin American countries address specific groups of patients, such as the obstetric outcome in childhood-onset SLE, 55 serum laminin-111 levels in preeclampsia and lupus, 56 as well as the gestational outcome in neuropsychiatric lupus 57 . Furthermore, a controlled clinical trial with a small number of patients showed the benefit of hydroxychloroquine on SLE activity during pregnancy 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Other published studies from Latin American countries address specific groups of patients, such as the obstetric outcome in childhood-onset SLE, 55 serum laminin-111 levels in preeclampsia and lupus, 56 as well as the gestational outcome in neuropsychiatric lupus. 57 Furthermore, a controlled clinical trial with a small number of patients showed the benefit of hydroxychloroquine on SLE activity during pregnancy. 37 Finally, not all of these previous studies have identified factors associated with poor obstetric outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Gradient descent is usually used to adjust the weights and node thresholds of the BP neural network. e following will briefly introduce the process of training BP network by gradient descent method [18]. e input vector is…”
Section: Learning Methods Of Bp Neural Networkmentioning
confidence: 99%
“…Therefore, we consider that this finding is not consistent with previous findings, probably due to lack of uniformity in the definitions, the different compositions of the cohorts, and differences in treatment regimens. 28,29 Considering these facts, pregnant SLE patients can be well-controlled based on the foundation of optimal management and medication adjustment. It should be noted, however, that currently available treatment options are largely still unstudied in this population.…”
Section: Discussionmentioning
confidence: 99%